Simulación de laboratorio para la realización de guías de Biología General en la Universidad Antonio Nariño (2023)
In the General Biology laboratories at the Antonio Nariño University, South Campus, several issues were identified. These issues include the lack of available laboratory spaces due to the high number of students requesting them, resulting in insufficient time for students to complete all practical activities. With only two hours per week allocated for these activities, it becomes challenging to successfully complete the laboratory work. Furthermore, students' inadequate preparation for practical activities leads to mishandling of laboratory equipment and tools, potentially additional material costs.